The Effects of Atypical Antipsychotic Usage Duration on Serum Adiponectin Levels and Other Metabolic Parameters - Elif Oral; Mustafa Gulec; Nezahat Kurt; Sumeyra Yilmaz; Nazan Aydin; Ismet Kirpinar (Eurasian Journal of Medicine, 2011)
Objective: Although atypical antipsychotics are well-tolerated and effective treatment options for schizophrenia, they have metabolic side effects, including weight gain and increased risk of Type II Diabetes Mellitus (DM). Adiponectin, produced exclusively in adipocytes, is the most abundant serum adipokine. Low levels of adiponectin are correlated with DM, insulin resistance and coronary heart disease. Usage of atypical antipsychotics may create a risk of metabolic syndrome. The aim of this study was to evaluate the effects of antipsychotic usage on parameters related to development of metabolic syndrome.Materials and Methods: A total of 27 patients (n=27) (13 women and 14 men) were recruited from our out-patient psychiatry clinic. All patients had been treated with atypical antipsychotics for at least 3 months and were in remission. Patients were evaluated for levels of HDL (High Density Lipoprotein), LDL (Low Density Lipoprotein ), TG (Triglyceride) total cholesterol and fasting blood glucose, body weight, BMI (Body Mass Index), waist circumference and serum adiponectin levels. Results: Serum adiponectin levels were significantly lower (p:0.000) and body weights were significantly higher (p:0.003) in the patients who had been using atypical antipsychotics for longer than a year in comparison to patients who had been using atypical antipsychotics for one year or less.Conclusion: Our findings supported the hypothesis that the length of administration of atypical antipsychotics has an effect on metabolic changes. They also highlight the fact that when investigating metabolic changes generated by atypical antipsychotic effects, the length of time that the patient has been on the atypical antipsychotics should also be considered.